Circular RNA hsa_circ_0051246 acts as a microRNA-375 sponge to promote the progression of gastric cancer stem cells via YAP1 - Deng,Minghui; Xu,Yefeng; Yao,Yongwei; Wang,Yiqing; Yan,Qingying; Cheng,Miao; Liu,YunXia (PeerJ, 2023)
Background Gastric cancer (GC) stem cells play an important role in GC progression. Circular RNAs (circRNAs) act as microRNA (miRNA) sponges and inhibit the biological function of miRNAs in GC cytoplasm. MiRNAs also participate in GC progress. circ_0051246 was shown to be associated with miR-375 after analyzing GC microarray data GSE78091 and GSE83521. The oncoprotein Yes-associated protein 1 (YAP1) is targeted by miR-375 and can be inactivated via the Hippo tumor suppressor pathway. Due to insufficient research on circ_0051246, this study aimed to investigate its relationship with miR-375 and YAP1 in cancer stem cells (CSCs). Methods SGC-7901 CSCs were used to establish knockdown/overexpression models of circ_0051246, miR-375, and YAP1. Malignant phenotypes of CSCs were assessed using Cell Counting Kit 8, colony/sphere formation, 5-Ethynyl-2′-deoxyuridine assay, flow cytometry, Transwell, and wound healing assays. To detect the interactions between circ_0051246, miR-375, and YAP1 in CSCs, a dual-luciferase reporter assay and fluorescence in situ hybridization were performed. In addition, 24 BALB/c nude mice were used to establish orthotopic xenograft tumor models. Four groups of mice were injected with CSCs (1 × 106 cells/100 µL) with circ_0051246 knockdown, miR-375 overexpression, or their respective control cells, and tumor progression and gene expression were observed by hematoxylin-eosin staining, immunohistochemistry. Western blot and quantitative real-time PCR were utilized to examine protein and gene expression, respectively. Results Circ_0051246 silencing reduced viability, promoted apoptosis, and inhibited proliferation, migration and invasion of CSCs. The functional effects of miR-375 mimics were comparable to those of circ_0051246 knockdown; however, the opposite was observed after miR-375 inhibitors treatment of CSCs. Furthermore, circ_0051246-overexpression antagonized the miR-375 mimics’ effects on CSCs. Additionally, YAP1 overexpression promoted CSC features, such as self-renewal, migration, and invasion, inhibited apoptosis and E-cadherin levels, and upregulated the expression of N-cadherin, vimentin, YAP1, neurogenic locus notch homolog protein 1, and jagged canonical notch ligand 1. Conversely, YAP1-silenced produced the opposite effect. Moreover, miR-375 treatment antagonized the malignant effects of YAP1 overexpression in CSCs. Importantly, circ_0051246 knockdown and miR-375 activation suppressed CSC tumorigenicity in vivo. Conclusion This study highlights the promotion of circ_0051246-miR-375-YAP1 axis activation in GC progression and provides a scientific basis for research on the molecular mechanism of CSCs.
Keywords: Gastric cancer; Cancer stem cells; Circular RNA; circ_0051246; microRNA; miR-375; Notch signaling pathway